ID 310 – Electromyography to protect the facial nerve during minimally invasive cochlear implantation. Issue 3 (March 2016) - Dür, C.; Ansó, J.; Rohrbach, H.; Stahl, C.; Ferrario, D.; Muntane, E.; Wyss, T.; Gerber, N.; Williamson, T.; Gavaghan, K.; Bell, B.; Weber, S.; et al.
Abstract : Objective: In minimally invasive cochlear implantation (MICI) a tunnel is drilled towards the middle ear cavity and the facial nerve (FN) appears exposed in close proximity to the tool (0.3–1.2 mm). No method has been reported to ensure intraoperative FN protection during drilling. A custom designed stimulation probe could enable a safe mechanism for early detection of the facial nerve during MICI. Methods: Per subject ( n = 5 sheep), 9 trajectories were drilled with different distances respect to the FN. Stimulus pulses with varying amplitude and duration were applied at 5 different depths. EMG responses were measured in the facial muscles. Measurements of drill to FN distance were achieved through μCT scans of the extracted temporal bones, postoperatively. A sensitivity and specificity analysis was performed for 3 stimulus threshold values (0.3, 0.5, 1 mA). Results: 90% of the detections with the bipolar electrodes occurred at the FN boundary. The 1 mA intensity and the monopolar electrode provided early detection of the FN (>0.2 mm). Conclusion: The newly developed probe has improved the sensitivity and specificity of FN detection during MICI. The results suggest that an insulated drill with monopolar stimulation at 1 mA would provide an early warning of FN detection above 0.2 mm.